Plasma oxylipin levels associated with preterm birth in preterm labor✰. (March 2021) - Svenvik, M.; Raffetseder, J.; Brudin, L.; Lindberg, R.; Blomberg, M.; Axelsson, D.; Jenmalm, M.C.; Ernerudh, J.; Nording, M.L.
Abstract: Introduction: Preterm labor is a common clinical problem in obstetrics. Since the majority of women with preterm labor eventually deliver at full term, biomarkers are needed to more accurately predict who will deliver preterm. Oxylipins, given their importance in inflammation regulation, are highly interesting in this respect since labor is an inflammatory process. Methods: Eighty women with preterm labor before 34 weeks of gestation were enrolled in a prospective observational multi-center cohort study. Oxylipin levels of 67 analytes in plasma samples were analyzed by liquid chromatography coupled to tandem mass spectrometry. Results: Twenty-one (26%) of the women delivered before 34 weeks of gestation, and of those women, fourteen delivered within 48 h of admission. Logistic multivariate regression showed that lower levels of 9, 10-DiHODE were associated with delivery before 34 weeks of gestation (aOR 0.12 (0.024–0.62)) and within 48 h ((aOR 0.13 (0.019–0.93)). Furthermore, higher levels of 11, 12-DiHETrE were associated with delivery before 34 weeks of gestation ((aOR 6.19 (1.17–32.7)) and higher levels of 8-HETE were associated with delivery within 48 h ((aOR 5.01 (1.13–22.14)). Conclusions: The oxylipin 9, 10-DiHODE may be protective in preterm labor, both for delivery after 34 weeks of gestation and for delivery later than 48 h of admission, whereas 11, 12-DiHETrE and 8-HETE display the opposite effect. Larger studies are needed to validate these mediators as biomarkers for prediction of preterm birth following preterm labor.